Rereading the victory discourses of liberalism—’the end of ideology’ and ‘the end of history’ (finalisation theories)—alongside the 2008 financial crisis - Atıl Cem Çiçek (Cogent Social Sciences, 2024)
The discourse of ‘the end of ideology’ put forward by Bell in 1960 was centred on the notion that an ideological consensus had been reached, especially in developed countries, and that ideologies were no longer necessary given that economic growth had replaced political growth as the predominant subject of debate. With the fall of the Berlin Wall and the collapse of real socialism in parallel to the breakup of the USSR, the discourse that liberalism constitutes the dominant and only paradigm rose dramatically in prominence alongside the neoliberal policies implemented following the economic crisis in the 1970s. Undoubtedly, one of the most important works in this trend was the ‘end of history’ thesis put forward by Fukuyama in the 1990s. This study is rooted in the need to reconsider these ‘finalisation’ theses founded on liberalism’s supposed lack of alternatives in the aftermath of the 2007–2008 global financial crisis. Offering a critique of historical economic-political liberalism, it aims to demonstrate the failure of these ending theses, both of which are still accepted and promoted by defenders of neoliberalism. This study employs historical and hermeneutic qualitative research methods. Its most important finding is that neoliberalism cannot be both a political and an economic ‘end’.